COMPREHENSION OF THE DESCRIPTIVE QUALITATIVE RESEARCH METHOD: A CRITICAL ASSESSMENT OF THE LITERATURE - Furidha, Brylialfi Wahyu (jfpublisher, 2023)
When a researcher comprehends the research, they can develop research methods because the research needs to adhere to scientific principles. Because of this matter, a methodical scientific approach is required to guarantee that the study can be reaffirmed by other researchers. Moreover, the descriptive qualitative method has become popular due to its less reliance on numerical values or metrics for variable measurement. The aim of this research is to provide a general review of the literature on descriptive qualitative research methods. The researcher can determine that qualitative descriptive research is a descriptively described research method that employs qualitative data based on the findings of the research. Analyzing events, phenomena, or social conditions is a common use for this kind of descriptive qualitative research. Furthermore, qualitative research does not rely on numerical measurements for its research object, nor does it employ statistical methods to test elaborative characteristics. Its application allows for the combination of different data collection techniques, data analysis, instrument creation, and other research stages commonly used in qualitative and descriptive research methodologies.